Chinese herbal compound prescriptions combined with Chinese medicine powder based on traditional Chinese medicine syndrome differentiation for treatment of chronic atrophic gastritis with erosion: a multi-center, randomized, positive-controlled clinical trial - Tai Zhang; Beihua Zhang; Jinkang Xu; Shunping Ren; Shaogang Huang; Zhaohong Shi; Shaoju Guo; Liqun Bian; Ping Wang; Fengyun Wang; Yidong Cai; Xudong Tang (BMC, 2022)
Abstract Background In this study, Chinese herbal compound prescriptions combined with Chinese medicine powder were evaluated for the treatment of chronic atrophic gastritis with erosion. Methods This multi-center, randomized, positive drug control clinical trial randomly assigned 216 patients with chronic atrophic gastritis with erosion to three groups: (1) control group: aluminum plus magnesium suspension thrice per day for 4 weeks; (2) test group 1: Chinese herbal compound prescriptions twice a day plus Sanqi (Panax notoginseng) powder twice a day for 4 weeks; (3) test group 2: Chinese herbal compound prescriptions twice a day plus Sanqi (Panax notoginseng) powder and Zhebeimu (Fritillaria thunbergii Miq.) powder twice a day for 4 weeks. The primary endpoint (improvement of gastric mucosal erosion; improvement of gastric mucosal pathology) and secondary endpoints (improvement of clinical symptoms scores; improvement of the patient-reported outcome [PRO] instrument for chronic gastrointestinal diseases) were assessed using endoscopy at week 4 following the treatment. Drug-related adverse events (AEs) and adverse drug reactions (ADRs) were also compared. Results The final analysis included 202 patients (control group, 63; test group 1, 69; test group 2, 70). At week 4, using within-group comparison, gastric mucosal erosion improved in each group following treatment with a significant difference (P < 0.05); there were no statistically significant differences in gastric mucosal erosion scores among the groups after treatment (P > 0.05); in terms of improvement of gastric mucosal erosion, the efficacy rate of the control group was 69.12%, the efficacy rate of the test group 1 was 73.24%, and the efficacy rate of the test group 2 was 69.01% and efficacy rate among the groups was not statistically significant (P > 0.05). As determined by acute inflammation, chronic inflammation, atrophy, intestinal metaplasia, and dysplasia, the pathological score (total score and the highest score) did not differ statistically among groups following treatment (P > 0.05); within the control group, the total scores of acute inflammation, chronic inflammation, atrophy, and intestinal metaplasia were significantly decreased (P < 0.05), but there was no significant improvement in dysplasia (P > 0.05); in the test group 1, chronic inflammation, atrophy, and intestinal metaplasia and dysplasia scores were significantly decreased (P < 0.05), but acute inflammation did not improve (P > 0.05); there was a significant reduction in the atrophy score in test group 2 (P < 0.05), but no improvement in the scores of acute inflammation, chronic inflammation, intestinal metaplasia, and dysplasia was observed (P > 0.05). Similarly, within the control group, the highest scores of acute inflammation, chronic inflammation, atrophy, and intestinal metaplasia were significantly decreased (P < 0.05), but there was no significant improvement in dysplasia (P > 0.05); there was a significant reduction in highest scores of atrophy, intestinal metaplasia, and dysplasia (P < 0.05) in test group 1, but the highest scores didn't not improve with acute inflammation and chronic inflammation (P > 0.05); there was a significant reduction in the highest atrophy score in test group 2 (P < 0.05), but no improvement in the highest scores of acute inflammation, chronic inflammation, intestinal metaplasia, and dysplasia was observed (P > 0.05). Compared to the control group, the main symptom scores and total symptom scores in the test groups were lower following treatment, with a statistically significant difference (P < 0.05); the analysis of covariance with center, erosion type, and group as factors was applied, and the comparison among the groups in dyspepsia, defecation, and total PRO instrument scores were statistically significant (P < 0.05). In the study period, AEs were reported in 3 (4.23%) patients in the test group 1 and 3 (4.41%) patients in the control group; ADRs were confirmed in 3 (4.23%) patients from the test group 1 and 2 (2.94%) from the control group. AEs and ADRs were not statistically significantly different among groups (AE, P = 0.2213; ADR, P = 0.2872). No serious AE or ADR was reported. Conclusions This study has shown that both aluminum plus magnesium suspension and Chinese herbal compound prescriptions together with Panax notoginseng powder are capable of improving gastric mucosal erosion and reducing gastric mucosal pathological scores, and there were no statistically significant differences among the groups in primary endpoints, indicating that Chinese herbal therapy can achieve similar efficacy than antacids in terms of primary outcomes. The aluminum plus magnesium suspension is comparable to Chinese herbal therapy in improving atrophy and intestinal metaplasia, and is inferior to Chinese herbal therapy in improving dysplasia. In addition, the Chinese herbal therapy significantly outperforms the aluminum plus magnesium suspension in improving symptoms. Therefore, the overall clinical outcome of Chinese herbal compound prescriptions together with Panax notoginseng powder based on TCM syndrome patterns in the treatment of erosive gastritis is superior to that of antacids. Trial registration ChiCTR, ChiCTR-IPR-15005905. Registered 22 January 2015, https://www.chictr.org.cn/showproj.aspx?proj=10359